The functional morphology and role of the thelycum in insemination, and its relation to the mating system in the seagrass shrimp Ambidexter symmetricus (Decapoda: Processidae). Issue 2 (20th May 2016) - Rasch, Jennifer A.; Bauer, Raymond T.
Abstract: There is considerable variation in structures known to function in the transfer and storage of sperm in female decapod crustaceans. The thelycum is a secondary sexual character that forms from the posterior thoracic sterna of female shrimps (especially penaeoids and sergestoids). Females in the caridean shrimp family Processidae have a thelycum‐like structure which rarely occurs in other caridean females. We tested the hypothesis that the processid thelycum serves as a spermatheca for either short‐term attachment or long‐term sperm storage. When inseminated females of the processid Ambidexter symmetricus were isolated after mating, newly spawned and then incubated embryos hatched, but in the continued absence of a male, females were unable to fertilize a subsequent spawn. Our observations on A. symmetricus show that sperm were not retained after female spawning, and thus the thelycum is not used for long‐term sperm storage as in many penaeoids. In A. symmetricus, the thelycum may serve as an external median spermatheca (seminal receptacle) for temporary attachment and storage of a sperm mass during the 2–3 h interval between mating and spawning. Observations on mating behavior support the hypothesis of a pure‐search (promiscuous) mating system in A. symmetricus, with males showing little interest before, and copulating with females only after, the female parturial molt. Mating encounters were short (<2 min). This mating system is like that of other caridean shrimps with populations structured similarly to those in A. symmetricus : a relatively high density of mobile individuals and sexual dimorphism in body size (reproductive females larger than males) but not in cheliped weaponry (similar in males and females).